Striatal Dopaminergic Function and Motor Slowing in Essential Tremor Plus - Kuusela, Aino M.; Honkanen, Emma A.; Jaakkola, Elina; Myller, Elina; Eklund, Mikael; Nuuttila, Simo; Murtomaki, Kirsi-Marja; Mertsalmi, Tuomas; Levo, Reeta; Ihalainen, Toni; Noponen, Tommi; Vahlberg, Tero; et al. (John Wiley & Sons, 2025)
Background: While previous imaging studies have generally shown normal striatal dopamine transporter (DAT) binding in essential tremor (ET), emerging evidence suggests a partial dopaminergic mechanism in this condition and an epidemiological link between ET and Parkinson's disease (PD). This link seems particularly meaningful in ET patients with additional neurological signs, such as slowness of movements, rigidity, or rest tremor (ET+).
Objectives: To investigate the potential dopaminergic pathophysiology of ET+ and to compare it to PD.
Methods: Fourty-three ET+ patients, 115 PD patients and 40 healthy controls were studied using [123I]FP-CIT SPECT imaging and clinical examinations. A median follow-up of 3.0 years was carried out to confirm the diagnoses. ET+ patients underwent an extended follow-up with a median of 7.7 years (range 4.3-9.8 years). Region-specific binding ratios of striatal DAT binding were compared among the groups and correlated with the MDS-UPDRS motor scores.
Results: Bradykinesia scores were negatively associated with posterior putamen DAT binding in both the ET+ and PD groups, with the strongest correlation observed in finger tapping (F = 11.1, β = -0.10, 95%CI -0.16 to -0.04, P = 0.001). In ET+ patients, kinetic tremor asymmetry correlated with posterior putamen DAT binding asymmetry (r = 0.33, P = 0.043), indicating a relationship between more severe tremor and subtle contralateral DAT loss.
Conclusions: In ET+, subtle increases in bradykinesia scores correlate with striatal dopaminergic dysfunction, while kinetic tremor asymmetry is associated with hemispheric DAT binding asymmetry. These findings support the concept of partial dopaminergic involvement in the pathophysiology of ET+.